Impact of social care supply on healthcare utilisation by older adults: a systematic review and meta-analysis. (29th August 2018) - Spiers, G; Matthews, F E; Moffatt, S; Barker, R O; Jarvis, H; Stow, D; Kingston, A; Hanratty, B
Abstract: Objective: to investigate the impact of the availability and supply of social care on healthcare utilisation (HCU) by older adults in high income countries. Design: systematic review and meta-analysis. Data sources: medline, EMBASE, Scopus, Health Management Information Consortium, Cochrane Database of Systematic Reviews, NIHR Health Technology Assessment, NHS Economic Evaluation Database, Database of Abstracts of Reviews of Effectiveness, SCIE Online and ASSIA. Searches were carried out October 2016 (updated April 2017 and May 2018). (PROSPERO CRD42016050772). Study selection: observational studies from high income countries, published after 2000 examining the relationship between the availability of social care (support at home or in care homes with or without nursing) and healthcare utilisation by adults >60 years. Studies were quality assessed. Results: twelve studies were included from 11, 757 citations; ten were eligible for meta-analysis. Most studies (7/12) were from the UK. All reported analysis of administrative data. Seven studies were rated good in quality, one fair and four poor. Higher social care expenditure and greater availability of nursing and residential care were associated with fewer hospital readmissions, fewer delayed discharges, reduced length of stay and expenditure on secondary healthcare services. The overall direction of evidence was consistent, but effect sizes could not be confidently quantified. Little evidence examined the influence of home-based social care, and no data was found on primary care use. Conclusions: adequate availability of social care has the potential to reduce demand on secondary health services. At a time of financial stringencies, this is an important message for policy-makers.